2017
DOI: 10.1016/j.toxlet.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Differential procoagulant effects of saw-scaled viper (Serpentes: Viperidae: Echis) snake venoms on human plasma and the narrow taxonomic ranges of antivenom efficacies

Abstract: Saw-scaled vipers (genus Echis) are one of the leading causes of snakebite morbidity and mortality in parts of Sub-Saharan Africa, the Middle East, and vast regions of Asia, constituting a public health burden exceeding that of almost any other snake genus globally. Venom-induced consumption coagulopathy, owing to the action of potent procoagulant toxins, is one of the most relevant clinical manifestations of envenomings by Echis spp. Clinical experience and prior studies examining a limited range of venoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
3

Relationship

6
3

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 55 publications
7
78
2
1
Order By: Relevance
“…3). Consistent with prior studies 36,37 , all of the tested viper venoms displayed net procoagulant activity, with the exception of B. arietans, which had no effect on plasma clotting ( The results of the SVMP and coagulation assays demonstrated that the peptidomimetic inhibitors outperformed the metal chelators and, although marimastat and batimastat are similar drugs in terms of both mechanism of action and in vitro efficacy, marimastat has a number of potential clinical advantages over batimastat, including: (i) increased solubility, (ii) excellent oral bioavailability vs. parenteral administration, and (iii) generally well tolerated vs. some reports of acute bowel toxicity 38 . Therefore, we selected marimastat as our candidate SVMP-inhibitor for use in vivo venom-neutralization experiments.…”
Section: Procoagulant Venom Activities Are Antagonized By Peptidomimesupporting
confidence: 92%
“…3). Consistent with prior studies 36,37 , all of the tested viper venoms displayed net procoagulant activity, with the exception of B. arietans, which had no effect on plasma clotting ( The results of the SVMP and coagulation assays demonstrated that the peptidomimetic inhibitors outperformed the metal chelators and, although marimastat and batimastat are similar drugs in terms of both mechanism of action and in vitro efficacy, marimastat has a number of potential clinical advantages over batimastat, including: (i) increased solubility, (ii) excellent oral bioavailability vs. parenteral administration, and (iii) generally well tolerated vs. some reports of acute bowel toxicity 38 . Therefore, we selected marimastat as our candidate SVMP-inhibitor for use in vivo venom-neutralization experiments.…”
Section: Procoagulant Venom Activities Are Antagonized By Peptidomimesupporting
confidence: 92%
“…Despite these identifications, and prior reports of PLA 2 s generally exerting anticoagulant activities (16), neither of these E. ocellatus PLA 2 s have previously been described as anticoagulants (33, 56, 57). Despite the venom from these species being potently procoagulant (7, 58), we only identified one XIC that could be correlated to a procoagulant bioactivity peak. This protein had a m/z -value of 1445.8645 35+ and a corresponding mass of 52015.873 Da, but could not be matched to a Mascot hit.…”
Section: Resultsmentioning
confidence: 96%
“…22 ). Notably, EchiTAbG also neutralised the procoagulant venom effects of seven of the remaining nine viper species, the colubrid snake D. typus and the natricine R. subminiatus , despite these latter two species having diverged from vipers over 54 million years ago 23 (Fig.…”
Section: Resultsmentioning
confidence: 99%